Synthesis of Bulk Zr48Cu36Al8Ag8 Metallic Glass by Hot Pressing of Amorphous Powders - Tianbing He; Nevaf Ciftci; Volker Uhlenwinkel; Sergio Scudino (Journal of Manufacturing and Materials Processing, 2021)
The critical cooling rate necessary for glass formation via melt solidification poses inherent constraints on sample size using conventional casting techniques. This drawback can be overcome by pressure-assisted sintering of metallic glass powders at temperatures above the glass transition, where the material shows viscous-flow behavior. Partial crystallization during sintering usually exacerbates the inherent brittleness of metallic glasses and thus needs to be avoided. In order to achieve high density of the bulk specimens while avoiding (or minimizing) crystallization, the optimal combination between low viscosity and long incubation time for crystallization must be identified. Here, by carefully selecting the time–temperature window for powder consolidation, we synthesized highly dense Zr48Cu36Ag8Al8 bulk metallic glass (BMG) with mechanical properties comparable with its cast counterpart. The larger ZrCu-based BMG specimens fabricated in this work could then be post-processed by flash-annealing, offering the possibility to fabricate monolithic metallic glasses and glass–matrix composites with enhanced room-temperature plastic deformation.